Political ecologies of cattle ranching in northern Mexico : private revolutions - Perramond, Eric (Society, environment, and place., 2010)
"In this study of the Rio Sonora region of northern Mexico, where ranchers own anywhere from several hundred to tens of thousands of acres, Eric Perramond evaluates management techniques, labor expenditures, gender roles, and decision making on private ranches of varying size. By examining the economic and ecological dimensions of daily decisions made on and off the ranch, he shows that, contrary to prevailing notions, ranchers rarely collude as a class unless land titles are at issue and that their decision making is as varied as the landscapes they oversee." "Through first-hand observation, field measurements, and intimate ethnographies, Perramond sheds light on a complex set of decisions made, avoided, and confronted by these land managers and their families. In particular he shows that ranching has endured because of its extended kinship network, its reliance on all household members, and its close ties to local politics." "Perramond follows ranchers caught between debt.